Possible Fenthion Toxicity in Magpies (Pica pica) - Hanson, J. (1981)
Unusual mortality in magpies (Pica pica) is described. Dead or sick birds were discovered in proximity to cattle in Alberta feedlots. Subsequent examinations indicated magpies were being exposed to fenthion, an organophosphate used on cattle for control of warble larvae and lice. The possibility of toxicity with fenthion is suggested.